Korelasi Dukungan Suami terhadap Pemberian Asi Eksklusif pada Ibu Menyusui (Lembaga Pengembangan Kinerja Dosen, 2025)
Exclusive breastfeeding (ASI) is the provision of only breast milk to infants for the first six months without additional food or drink, including water. Breast milk has important benefits in improving infant health, growth, and survival. However, the coverage of exclusive breastfeeding in Indonesia, including in the Pasar Health Center in Prabumulih City, has not yet reached the national target of 80%. One factor influencing the success of exclusive breastfeeding is husband's support. The purpose of this study was to determine the correlation between husband's support and exclusive breastfeeding. The study used a quantitative approach with a cross-sectional design. The sample size was 49 mothers with infants aged 7–12 months. The study was conducted in the Pasar Health Center in May 2025. The results showed that 28 infants (57.1%) received exclusive breastfeeding, and 30 mothers (61.2%) reported receiving support from their husbands. Statistical tests using the chi-square test showed a significant relationship between husband's support and exclusive breastfeeding (p = 0.000). These findings indicate that husband's support plays an important role in successful breastfeeding. This research suggests that involving husbands in breastfeeding education and support is highly recommended to increase the coverage of exclusive breastfeeding in the community.